Somewhere Over the Verde Rainbow - Ekart, Donna F. (My University, 2008)
ERMs are the future of serials management for academic libraries, but no one is quite sure what that future will look like. Lessons learned during Verde ERM implementation from K-State Libraries at Kansas State University.
Keywords: Verde; Libraries; ERM; Electronic resources; Implementation; Planning